1996
DOI: 10.1021/jf9503725
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Identification of Antioxidant Components from the Leaves of Mulberry (Morus alba L.)

Abstract: The antioxidant activity of mulberry leaves (Morus alba var. Acidosa G. cv. Taisang 2) was investigated. The results indicated that methanolic extracts of mulberry leaves (MEML) showed stronger antioxidant activity and that methanol gave higher yields of extract than other organic solvents. The MEML exhibited 78.2% inhibition on peroxidation of linoleic acid, greater than that of R-tocopherol (72.1%) but equal to that of butylated hydroxyanisole. The MEML were separated into nine fractioins by thin-layer chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 13 publications
9
42
1
4
Order By: Relevance
“…It was reported that solubility of the phenolic compounds increases with polarity of extracts (Siddhuraju and Becker 2003;Sultana et al 2007) and polarity of MeOH is the highest among the three solvents used in this study. MeOH is a highly preferred solvent for the extraction of phenols (Yen et al 1996). Similarly, total flavonoid content was also found to be highest in MeOH extract (p \ 0.05) and an earlier report (Mohamed et al 2010) showed increase in yield of flavonoid from Mirabilis jalapa tubers due to extraction using solvents of increasing polarity.…”
Section: Discussionmentioning
confidence: 72%
“…It was reported that solubility of the phenolic compounds increases with polarity of extracts (Siddhuraju and Becker 2003;Sultana et al 2007) and polarity of MeOH is the highest among the three solvents used in this study. MeOH is a highly preferred solvent for the extraction of phenols (Yen et al 1996). Similarly, total flavonoid content was also found to be highest in MeOH extract (p \ 0.05) and an earlier report (Mohamed et al 2010) showed increase in yield of flavonoid from Mirabilis jalapa tubers due to extraction using solvents of increasing polarity.…”
Section: Discussionmentioning
confidence: 72%
“…is an economically important tree grown in India, China, Korea and several Asian countries where its foliage is used as food for silkworms in sericulture industry (Vijayan et al 2012). It is also commercially valuable in the horticulture, food and cosmetic industries, in particular, its phytochemical and medicinal properties such as antioxidants (Yen et al 1996) and hypoglycemia compounds (Kelkar et al 1996) have been widely used as healthcare products. These days it is cultivated for fruit production, which is used for human consumption including jam, jelly, frozen desserts, pulp, juice and wine (Koyuncu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…From the data obtained, methanol was found to be the effective solvent for the extraction of phenolic components. Previously reported data also recommend methanol as the better solvent for phenolic compounds extraction 18,19 . However, TFC was obtained in good yield in the ethanol extract of J. adhatoda flower (40.8 ± 4.1 mg/100 g) followed by the methanol extract of L. camara flower (20.1 ± 1.9 mg/100 g).…”
Section: Discussionmentioning
confidence: 94%